THE LINGUISTIC AND HISTORICAL BACKGROUND OF VASYL STEFANYK’S CORRESPONDENCE (BASED ON LETTERS TO IVAN FRANKO) - Brus, Mariia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
This article focuses on the development of Vasyl Stefanyk’s creative work during the late 19th and early 20th centuries, a period marked by the revival of Ukrainian identity, nationality, and the native language. Given the dialectal basis of his literary and epistolary works, which reflected the rich and colorful speech of the Rusyn dialect, he can be considered a successor to the representatives of the “Rusyn Trinity” and a proponent of the idea of creating a unified Ukrainian literary language based on the living vernacular.Using Vasyl Stefanyk’s correspondence as an example, the study demonstrates that the Western Ukrainian region and the Pokutsk dialect contain a significant number of historical linguistic elements that have fallen into disuse or disappeared entirely from the literary language, and have largely been preserved in the dialects of the Ukrainian language, particularly those of the southwestern dialect group. These elements pertain to various levels of the Ukrainian language’s development: phonetic, lexical, morphological, and syntactic. It is noted that they can not only reconstruct the history of the development of specific features of the Ukrainian language preserved in its dialects but also confirm the fact that the continuous and long-term development of the Ukrainian literary language occurred on its own historical basis.